2020
DOI: 10.1257/jep.34.2.24
|View full text |Cite
|
Sign up to set email alerts
|

A Century of the American Woman Voter: Sex Gaps in Political Participation, Preferences, and Partisanship since Women’s Enfranchisement

Abstract: This year marks the centennial of the Nineteenth Amendment, which provided American women a constitutional guarantee to the franchise. We assemble data from a variety of sources to document and explore trends in women’s political participation, issue preferences, and partisanship since that time. We show that in the early years following enfranchisement, women voted at much lower rates than men and held distinct issue preferences, despite splitting their votes across parties similarly to men. But by the dawn o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 2 publications
2
12
0
Order By: Relevance
“…Voting patterns differ between men and women with respect to social policy, so perhaps it should be expected to carry over to their preferences for fields of study in economics. Women have become increasingly motivated to participate in politics over time, with successive generations since suffrage demonstrating ever more political mobilization (Cascio & Shenhav, 2020). Shapiro and Mahajan (1986) found that women were more likely to support government action on “compassion” issues to do with social welfare and to favor spending and regulation with the aim of environmental protection.…”
Section: Women and Men And Economicsmentioning
confidence: 99%
“…Voting patterns differ between men and women with respect to social policy, so perhaps it should be expected to carry over to their preferences for fields of study in economics. Women have become increasingly motivated to participate in politics over time, with successive generations since suffrage demonstrating ever more political mobilization (Cascio & Shenhav, 2020). Shapiro and Mahajan (1986) found that women were more likely to support government action on “compassion” issues to do with social welfare and to favor spending and regulation with the aim of environmental protection.…”
Section: Women and Men And Economicsmentioning
confidence: 99%
“…Our aims are different, characterizing the risk of a close election and comparing this risk to single-tier systems. Our work also connects to recent econometric studies at the intersection of demographics and voting power over US history, including Cascio and Washington (2014), Kuziemko andWashington (2018), andShenhav (2020). 11 Hirsch is concerned primarily with the ability of electronic election tallies to be hacked in a close statewide race.…”
Section: Introductionmentioning
confidence: 92%
“…These gendered patterns of citizenship and exclusion are amplified in daily interactions with the state, as women seek to access rights and resources (Korteweg 2003(Korteweg , 2006; The gendered structure of citizenship and power have yielded gendered patterns in political engagement. Although women have lower rates of most forms of political participation, they have voted at somewhat higher rates than men since the 1980s (Cascio and Shenhav 2020;Schlozman et al 1995), perhaps because they are more likely to have regular interactions with the government or possibly as a reaction to the assault on women's rights (Carreras 2018;Cascio and Shenhav 2020;Rampell 2014;Stauffer and Fraga 2021).…”
Section: Gender Politics and Votingmentioning
confidence: 99%